(untitled) (CIPEEX, 2025)
Objective liability of the State is characterized by the absence of the need to prove the agent’s fault, requiring only three elements: administrative act, damage, and causal link[1]. The administrative act covers any conduct attributable to the Public Administration, even if performed by an agent outside their official duties. Damage may be material or moral, and its proof is essential. The causal link requires that the harm directly results from the State’s conduct, excluding liability in cases of third-party actions or exclusive fault of the victim. Objective liability also applies to lawful administrative acts, provided the elements are present, as recognized by the Brazilian Supreme Court in cases of state intervention in the economic domain. The burden of proof may be reversed, requiring the State to demonstrate the absence of the liability elements. Contributory fault may reduce or exclude compensation, and unforeseeable events such as force majeure or fortuitous events may also exempt the State, depending on their inevitability and unpredictability.